(3ffGFL GdaWfI aj fXe cdjdI hOefIs - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s; (3HjOHGs
(3ChdgG (B:s
(3GdMeO ddg GdYdj TGfg GdbGgQ GdPj YdG HQgGofg s
(3BNQgG (B:s
(3Ke hbaJ Ydi eShOJg HNWg abGHdJ fSNJj hUMMJgG, hhQOJ ajgG eG cGf YReg s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B128 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs